2022
DOI: 10.1007/s11947-022-02943-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Applications to Control Patulin Produced by Penicillium expansum CMP-1 in Apple Products and Study of Further Patulin Degradation Products Formation and Toxicity

Abstract: Patulin is a mycotoxin whose presence in apple-derived products and fruit juices is legally regulated, being its maximum limits established in the legislation of multiple countries. However, the management of contaminated batches is still an issue for producers. This investigation aims to evaluate ultraviolet light (254 nm, UV-C254nm) irradiation to find solutions that can be applied at different stages of the apple juice production chain. In this regard, 8.8 (UV-1) and 35.1 (UV-2) kJ m−2 treatments inactivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Diao et al [91] also revealed that UV irradiation of apple juice significantly decreased patulin from 99.42 µg/L to 16.98 µg/L (82.92% reduction) after exposure for 5 min at UV intensity of 3.8 mW/cm 2 . Additionally, it was shown that the treatment of apple juice containing patulin with UV light (254 nm and 450 kJ/cm 2 ) resulted in more than 98% reduction in patulin and at the same time an inactivation of the spores of Penicillium expansum [92].…”
Section: Patulin Treatmentmentioning
confidence: 99%
“…Diao et al [91] also revealed that UV irradiation of apple juice significantly decreased patulin from 99.42 µg/L to 16.98 µg/L (82.92% reduction) after exposure for 5 min at UV intensity of 3.8 mW/cm 2 . Additionally, it was shown that the treatment of apple juice containing patulin with UV light (254 nm and 450 kJ/cm 2 ) resulted in more than 98% reduction in patulin and at the same time an inactivation of the spores of Penicillium expansum [92].…”
Section: Patulin Treatmentmentioning
confidence: 99%
“…The virulence of the pathogen is closely related to hosts (species and developmental stages) and environmental conditions (temperature, humidity, light type and intensity, atmosphere composition, pH, etc.) [6][7][8][9][10]. Physical control approaches generally aim to optimize environmental parameters to balance inhibitory efficiency and energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…A survey report on patulin in apple juice and other apple products stated that there are no maximum levels (MLs) for patulin in the Australia New Zealand Food Standards Code, instead, patulin levels should be kept as low as reasonable and food must be safe for human consumption (Food Standard Australia and New Zealand, 2023). Notwithstanding these laws, the presence of PAT in food commodities across the world remains a problem for food sectors (particularly fruit and juice processors), and foods exceeding the stated limitations are still observed (Nicolau-Lapeña et al, 2023).…”
mentioning
confidence: 99%